How healthy are chronically ill patients after eight years of homeopathic treatment? - Results from a long term observational study - Mengler Nils; Lüdtke Rainer; Witt Claudia M; Willich Stefan N (BMC, 2008)
Abstract Background Homeopathy is a highly debated but often used medical treatment. With this cohort study we aimed to evaluate health status changes under homeopathic treatment in routine care. Here we extend former results, now presenting data of an 8-year follow-up. Methods In a prospective, multicentre cohort study with 103 homeopathic primary care practices in Germany and Switzerland, data from all patients (age >1 year) consulting the physician for the first time were observed. The main outcome measures were: The patients' perceived change in complaint severity (numeric rating scales from 0 = no complaint to 10 = maximal severity) and quality of life as measured by the SF-36 at baseline, and after 2 and 8 years. Results A total of 3,709 patients were studied, 73% (2,722 adults, 72.8% female, age at baseline 41.0 ± 12.3; 819 children, 48.4% female, age 6.5 ± 4.0) contributed data to the 8-year follow-up. The most frequent diagnoses were allergic rhinitis and headache in adults, and atopic dermatitis and multiple recurrent infections in children. Disease severity decreased significantly (p < 0.001) between baseline, 2 and 8 years (adults from 6.2 ± 1.7 to 2.9 ± 2.2 and 2.7 ± 2.1; children from 6.1 ± 1.8 to 2.1 ± 2.0 and 1.7 ± 1.9). Physical and mental quality of life sores also increased considerably. Younger age, female gender and more severe disease at baseline were factors predictive of better therapeutic success. Conclusion Patients who seek homeopathic treatment are likely to improve considerably. These effects persist for as long as 8 years.